Analisis Faktor Determinan Mediko Sosial Pada Ibu Dengan Anak Stunting Di Kabupaten Mamuju Provinsi Sulawesi Barat - karsa, nevi sulvita; Mappaware, Nasrudin Andi; Latief, Shofiyah; Irwan, Andi Alamanda; Pangnguriseng, Utomo Andi (Green Medical Journal, 2021)
Introduction: Stunting is a linear growth disorder caused by malnutrition in chronic nutrient intake and chronic recurrent infectious diseases as indicated by height z-score according to age. Infancy is a period that is very sensitive to the environment so more attention is needed especially the adequacy of nutrition. Obstetric complications are very influential on several determinant factors, one of these factors is a medical society or social risk. Family socioeconomic status such as family income, parental education, mother's knowledge about nutrition, and the number of family members can indirectly relate to stunting. Methods: A cross-sectional analytic with a retrospective approach. Processing data using regression tests. Result: The results of this Stunting study were obtained from nutritional status data on children under five in the province of West Sulawesi in January-June 2020 by taking samples using simple random sampling. The total number of samples in this study were 88 people taken from mothers who have Stunting children aged 2-5 years. Social risk is the condition of the mother during pregnancy including age, level of education, ethnicity, occupation, income, referral decision, cost considerations, distance traveled, referral mobilization, consideration of health insurance that is expected to be related to stunting. Conclusion: In this study, it was found that the most influential medicosocial determinants were referral mobilization and employment.